Applications for self-management of type 1 diabetes in users of continuous insulin infusion system - Albuquerque Brandão, Maria Girlane Sousa (2023)
Objetive: To identify and understand the characteristics of mobile applications for self-management of type 1 mellitus diabetes in users of continuous insulin infusion systems.                                                                 Method: integrative review with searches carried out in the month of June 2020, based on the articles published in PUBMED, CINAHL, Cochrane Library, Web of Science and Scopus. The eligibility criteria were based to consider those studies that addressed mobile applications for self-management of DM1 in users of Continuous Infusion System of Insulin without time restriction. Only unavailable studies were excluded.                                                                                                          Results: After the analysis of two independent reviewers, 14 studies were included in the final analysis, and 11 mobile applications for smartphones that can assist in self-management of DM1 were identified; these were named as iDECIDE, Sugar Sleuth, VoiceDiab, Blip, GoCARB, Nightscout, Intelligent Diabetes Management, Calculator Food exchange mobile, Insulin Pump, DiaMob and Interactive Diary on Diabetes.                                                                                       Conclusion: Mobile applications were developed to promote behavioral changes and treatment adjustments in a positive way, both in clinical results and in the quality of life and self-management of diabetes in people with DM1. Mobile apps for smartphones can assist in self-management of DM1 by enabling assistance in the decision to apply insulin, glycemic control, analysis of the need for insulin in meals, food management, calculation of food components in meals, continuous glucose monitoring and automatic calculation of bolus of carbohydrates and insulin.